Uso del merchandising visual y la fidelización de los clientes del Centro Dermatológico Integral Cromwell Angulo, Trujillo, 2021 - Alva Carranza, Laura Soledad (2021)
This work was carried out in order to determine the relationship between the use of visual merchandising and the loyalty of the clients of the Integral Dermatological Center Cromwel Angulo, Trujillo, 2021. The problem formulated for the research was: What is the relationship between visual merchandising and customer loyalty at the Cromwell Angulo Integral Dermatological Center, Trujillo, 2021? and it was proposed as hypothesis: The use of visual merchandising has a direct relationship in the loyalty of the clients of the Cromwell Angulo Integral Dermatological Center in the city of Trujillo, 2021.The research design used was non-experimental correlational. Regarding the techniques, the interview and survey were used; and the interview guide and the questionnaire were used as an instrument. As a result, the use of visual merchandising has a direct relationship in the loyalty of the clients of the Integral Dermatological Center Cromwell Angulo, Trujillo, 2021 since with the improvements made in the setting of the establishment the preference for the service is reinforced.